PENGARUH KETERAMPILAN GURU DALAM PENGELOLAAN KELAS TERHADAP HASIL BELAJAR EKONOMI BISNIS SISWA KELAS X DI SMK PGRI PEKANBARU - Nuraini Nuraini; Sri Kartikowati; Sumarno Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of teacher skills in class management on the learning outcomes of Business Economics student class X SMK PGRI Pekanbaru. The population is 145 students and sample is 106 responden, taken by simple random sampling techniqgue. Data were collected through questionnaires and documentation. Result of research based on simple linear regression of teacher skill in class management have positive effect to result of learning, can with regression equation 24,286 + 0,947. Judging from Determination R2 obtained niali of 0.339. This means that teachers' skills in classroom management (X) contribute 33.9% of learning outcomes (Y). Keyword: Classroom management skills and learning outcomes